2020
DOI: 10.1080/21548331.2020.1762366
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and treatment of neurological and psychiatric disorders among tertiary hospitals in Pakistan; findings and implications

Abstract: Introduction: Mental health and neurological disorders are prevalent in Pakistan. However, there are considerable concerns with their management due to issues of access, availability of trained personnel and stigma alongside paucity of such data. Consequently, there is a need to document current treatment approaches starting with tertiary hospitals in Pakistan where patients with more severe mental and neurological disorders are typically treated. Subsequently, use the findings to help direct future policies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 87 publications
0
7
1
Order By: Relevance
“…34,35 However, our study prevalence was higher than other studies from Madonna University Teaching Hospital in Pakistan and Saudi Arabia. [36][37][38] In addition, our findings were lower than the 10-year trends reported in China and the Democratic Republic of Korea. 39,40 The characteristics of the study participants, study designs, socioeconomic status, cultural context, study setting, methodology, and diagnostic tools employed and sample size may all contribute to the differences between studies that have been observed.…”
Section: Discussioncontrasting
confidence: 97%
“…34,35 However, our study prevalence was higher than other studies from Madonna University Teaching Hospital in Pakistan and Saudi Arabia. [36][37][38] In addition, our findings were lower than the 10-year trends reported in China and the Democratic Republic of Korea. 39,40 The characteristics of the study participants, study designs, socioeconomic status, cultural context, study setting, methodology, and diagnostic tools employed and sample size may all contribute to the differences between studies that have been observed.…”
Section: Discussioncontrasting
confidence: 97%
“…We started in hospitals in view of the critical role for institutions such as DTCs in improving prescribing in hospitals through joint activities; however, we are aware that DTCs can be very variable within LMICs and that there can be extensive activities by pharmaceutical companies influencing prescribing (Fadare et al, 2018a;Fadare et al, 2018b;Ogunleye et al, 2019). We are also aware that there can be considerable concerns with the prescribing of medicines in hospitals in Pakistan (Saleem et al, 2019;Khan et al, 2020b). We chose Punjab for this initial study as it is the most populous province in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Yearly, about 1.5 million people die from TBI and those several millions that survive receive emergency treatment (Hien & Chae, 2011). Neurological injuries affect 1.4 million people per year in Pakistan (Khan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%